A literature review on the impact of disasters on healthcare systems, the role of nursing in disaster management, and strategies for cancer care delivery in disaster-affected populations - Wang, Wen; Li, Hui; Huang, Miao (Frontiers in Oncology, 2023)
This review article highlights the critical role of nurses in disaster management, with a specific focus on addressing blood tumors in disaster-affected populations. Disasters have a significant impact on healthcare systems and populations, and nurses play a crucial role in disaster preparedness, response, and recovery. The article provides case studies and successful examples of nursing interventions in disaster settings and tumor management, emphasizing the challenges and opportunities in providing cancer care in disaster settings. Recommendations for future research and practice in disaster nursing and blood tumor care are also presented. This information is essential for healthcare professionals and policymakers involved in disaster management, as well as researchers and clinicians working in the field of cancer care.